WHY THE BALTIC COUNTRIES CHOSE NOT TO DEVALUE THEIR CURRENCIES: THE POLITICAL PERSPECTIVE - Kuokštis, Vytautas (Politologija, 2015)
The article addresses the question of why the Baltic countries chose internal devaluation over external devaluation in response to the economic crisis of 2008–2010. After describing the situation in the Baltics and the two main choices, the paper argues that economic explanations are insufficient in accounting for the choice. Several political explanations for the choice are laid out based on external pressure arguments, society-oriented perspective and institutional perspective. The paper finds that the external pressure hypothesis is unable to account for the Baltic decision, which rather reflected a very strong domestic consensus on the importance of safeguarding fixed exchange rates. This consensus in turn was based on both widespread support by the general society and concentrated producer groups. Nevertheless, society-oriented perspective cannot fully explain the Baltic choice either – economic policies pursued during the crisis can only be fully understood when analyzing specific historical conditions under which the fixed exchange rate institutional system and its supporting elements were created. Over time, self-enforcing effects of the system became apparent both in the ideational sphere (principled beliefs about nationhood as well as particular causal beliefs) and in the material one, largely through the credit channel (indebtedness in euros). The current crisis also witnessed tendencies largely reinforcing the institutional equilibrium that supports the fixed exchange rate system.